A retrospective study of patients with biologics treatment at Groote Schuur and Red Cross Children's War Memorial Hospitals - Ahmed, Mohammed Awad Eltoum (Department of Medicine, 2020)
Introduction. The high cost and concern of adverse events, particularly infections, limit the use of biologic disease-modifying anti-rheumatic (bDMARD) therapies. We undertook this retrospective study to document their use for immune-mediated diseases (IMDs) and explore the efficacy, safety, adherence and screening practices prior to initiating bDMARDs in a tertiary referral hospital. Methods. A folder review of all adult and paediatric patients treated for IMDs with bDMARDs at Groote Schuur and Red Cross Hospitals between January 2013 and December 2019. Clinico-demographic particulars, details of bDMARD therapy, and adverse events were collated. Changes in disease activity were measured by diseasespecific tools at 6, 12, 24-months and at the last available visit, and patient adherence to bDMARDs was explored by folder and pharmacy record review. Results. We studied 151 folders, with 182 bDMARDs uses (29 patients used more than 1 bDMARD). Patients were from rheumatology (n= 38: 13 rheumatoid arthritis; 10 spondyloarthritis, 5 Systemic Lupus Erythematosus (SLE) , 5 inflammatory myositis and 5 other conditions); gastroenterology (n=31; 26 Crohn`s and 5 Ulcerative Colitis), dermatology (n=9; psoriasis), neurology (n=4, ophthalmology (n= 25; 6 scleritis, 18 uveitis, 1 optic neuritis), and paediatrics (n= 45, 26 juvenile idiopathic arthritis , 12 SLE, 7 other conditions). The bDMARDs used were TNF inhibitors (112), rituximab (55), tocilizumab (10), anakinra (3), abatacept (1), and tofacitinib (1). The vast majority of patients had an excellent response and were in low disease activity or remission at their last available visit. Adverse events included severe infection (4), tuberculosis (TB) (2), mild infection (4), severe allergic reaction (3), mild skin reaction (14), elevated liver enzymes (2), and worsening interstitial lung disease ILD (1). bDMARD Therapy was discontinued in 18 patients, most commonly due to adverse reaction (9), lack of response (3), poor adherence (2), or remission (1). bDMARD Therapy was changed to alternative therapy in 29 patients, most commonly because of poor response (14), or adverse effects (9) or poor adherence (3). Poor adherence or patients lost to follow-up was noted in 18/182 (9.9%). Complete latent TB infection screening with chest x-ray and TB skin test was performed in only 55 (36.4 %) but INH prophylaxis was given to 51/88 (57.9%) of patients prescribed TNFi therapy. Hepatitis B screening performed in 93 (61.6 %) patients, but most patients (72.2 %) were not tested for Hepatitis B core ab. Hepatitis C screening was performed in 81 (53.6 %) patients. Only 88 (58.3%) patients had a recent HIV test. The majority (17.2%) received the influenza vaccine, but only 24 (15.8 %) received pneumococcal vaccination. Discussion and Conclusion. bDMARD therapy was an effective treatment, and the most common adverse effect was infection (7.2%), with 2 TB infections. Vaccination and screening for TB, viral hepatitis and HIV was suboptimal. Of concern, poor adherence to bDMARDs was frequently encountered.